And trauma became flesh: terrorism, violence and trauma in Elnathan John’s born on a Tuesday and Helon Habila’s the Chibok girls (2018)
Literature and terrorism presents an interesting burgeoning field of discourse, especially in the literary and critical enterprise of the post- 9/11 years. This study explores the intersection of terrorism, violence and trauma in Elnathan John’s Born on a Tuesday and Helon Habila’s The Chibok Girls. It applies theoretical and critical insights from the trauma theory to the reading of the two purposively selected texts- John’s Born on a Tuesday and Habila’s The Chibok Girls. The writers’ depiction of the complex nuances of pain, terror, conflict and survival pangs experienced by Dantata, Banda, the Chibok Girls, and the entire northern region in Nigeria, bear witness to the physical, psychological, sociocultural, spiritual, environmental and insidious traumas inflicted upon individuals as well as the community. On the personal and collective levels, trauma has become flesh, and made its dwelling among the populace. Through the employment of such tropes and motifs as repetition compulsion, the trauma trope, the shattering trope, escapism, and the death drive, John and Habila unearth the structures that allow for the perpetuation of trauma and the mechanisms that entrench trauma across the northern Nigeria. John’s Born on a Tuesday and Habila’s The Chibok Girls attest to how violent conflicts and religious extremism interweave in a complex traumatizing network that continues to sear the Nigerian sociocultural and political space.